Association between Obesity and COVID-19 Outcomes in the Intensive Care Unit of RSUP Dr. M. Djamil Padang - Ilham Ilham; Fenty Anggrainy; Dessy Mizarti (Perhimpunan Dokter Paru Indonesia (PDPI)/The Indonesian Society of Respirology (ISR), 2022)
Background: Obesity is one of the risk factors for severe clinical COVID-19. This is because these patients tend to have comorbidities such as metabolic disease and cardiovascular disease. Obesity may result in poor outcomes, such as prolonged hospital stays, higher incidence of ARDS and mortality. The purpose of this study was to determine the correlation between obesity and the outcome of confirmed COVID-19 patients.Methods: This was an analytical study with retrospective cohort design on COVID-19 patients treated in the intensive care unit (ICU)of RSUP Dr. M. Djamil Padang. Data were taken from patients’ medical records between November 2021 and February 2022. The correlation between obesity with length of stay and patient mortality was analyzed using Chi-square test. Odds ratio was also assessed.Results: This study obtained that the characteristics of obese COVID-19 patients were mainly women (54.20%). The most dominant age group was 60-69 years (31.3%). About83.3% of obese patients were found to be clinically critical. Inflammatory markers such as procalcitonin, ferritin, IL-6 and d-dimer were not significantly associated with obesity. Diabetes mellitus was significantly related to the outcome of COVID-19 patients with obesity and without obesity (0.009%). Obesity was not correlated with hospital length of stay of COVID-19 patients, but was significantly associated with length of stay in the ICU [OR 3.67 (95% CI, 1.09-12.35)]. Obesity was significantly associated with mortality [OR 2.84 (95% CI, 1.12-7.18)] and length of conversion for COVID-19 patients in the ICU [OR 30.00 (95% CI, 2.85-31, 61)]. The expansion of adipose tissue both subcutaneously and viscerally which could be observed in obese patients can increase the proinflammatory, prothrombotic, and vasoconstrictive state that might affect the clinical deterioration of COVID-19 patients. This condition also manifests as insulin resistance, hypertension, atherosclerosis, cardiovascular disease and immunocompromised conditions which can generate high mortality rate.Conclusion: Obesity was found to be significantly associated with mortality, conversion time and length of stay for COVID-19 patients in the ICU.